SOCIAL WORK IN SCHOOL EDUCATION - Siedlaczek-Szwed, Aleksandra; Jałowiecka-Frania, Agata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This work comments on issues connected with an aspect to include tasks from widely perceived social work into the activity of school. School, by fulfilling certain social tasks, consolidates characteristics which are significant for workplaces, as well as social institutions, e.g. children’s homes, community centres, social units. Thus, for a student, school is some kind of mind training department. The time spend at educational facility forces, apart from didactical activities, insurance that children in care will get a possibility to relax, play or to provide safe development, then by defined part of a day the school replaces a family. Didactical functions, character and social education of school are equal and mutually connected. By understanding social work within categories of support in gaining abilities of self functioning within society, it will be then an activity which includes various behaviours and attitudes which drive to equip a client with necessary strength or means which are crucial for individual development and proper social functioning.